EPEN-11. TUMOR DIFFERENTIATION IMPACTS THE BIOLOGY OF RECURRENCE IN CHILDHOOD POSTERIOR FOSSA EPENDYMOMA. (1st June 2021) - Donson, Andrew; Ritzmann, Timothy; Willard, Nicholas; Griesinger, Andrea; Amani, Vladimir; Harris, Faith; Grimaldo, Enrique; Sanford, Bridget; Riemondy, Kent; Hankinson, Todd; Grundy, Richard; Foreman, Nicholas
Abstract: Ependymoma (EPN) of childhood is curable in only 50% of cases, with recurrences in the remainder that are refractory to treatment. In recent years significant advances have been made in understanding the molecular and cellular biology of EPN. Recent studies show that PFA subgroup EPN are comprised of multiple neoplastic subpopulations that show undifferentiated, differentiated and mesenchymal characteristics. These studies focused on tumor at presentation, with recurrent EPN being less well understood. In the present longitudinal study we examine changes in neoplastic cell heterogeneity in serial presentations of PFA EPN using deconvolution (Cibersort) of bulk RNAseq data. Analysis of a cohort of 48 PFA EPN presenting at Children's Colorado showed survival and PFA1/PFA2 subtype assignment was associated with the proportion of individual neoplastic subpopulations as determined by deconvolution. Tumors that subsequently regrew had a significantly higher estimated proportion of undifferentiated EPN cells (UEC) at presentation, than those that were non-recurrent after 5 years follow-up. This outcome association potentially age related, as UEC proportions are significantly higher in PFA arising in children < 1 year old who have a particularly poor prognosis. Changes in PFA neoplastic subpopulations at recurrence was performed in two cohorts of patients from Children's Colorado (n=23) and Nottingham, UK (n=15). As a whole, no subpopulation proportion was significantly changed at recurrence. However, separation of PFA into subtypes PFA1 and PFA2 revealed an increase in the proportion of the cilia-differentiated EPN cell subpopulation is more frequent event in PFA1 (15/24), and rare in PFA2 (2/11). Changes in other neoplastic subpopulations at recurrence were smaller and only seen in PFA1, both UEC and mesenchymal subpopulations being lower at recurrence. In summary, only PFA1 showed dynamic changes in neoplastic subpopulation proportions at recurrence, with potential impacts on transcriptomic based-subgroup assignment, whereas PFA2 proportions remained largely stable.